Land‐use legacies limit the effectiveness of switches in disturbance type to restore endangered grasslands. (30th November 2020) - Price, Jodi N.; Schultz, Nick L.; Hodges, Joshua A.; Cleland, Michael A.; Morgan, John W.
Abstract : Temperate native grasslands in Australia have been decimated across their range since European colonization (>200 years ago), and the few remaining remnants are mostly fragmented and degraded. Changes in disturbance type, particularly the removal of Indigenous fire and the introduction of livestock grazing, resulted in the local extinction of fire‐dependent and grazing‐sensitive native species, and led to an increase in exotic species. Recently, native grasslands have been acquired to improve the reservation status of the threatened community and management strategies have been implemented that involve the removal of livestock grazing and the reintroduction of fire or other biomass reduction methods. Here, we examine if the change in disturbance type—a disturbance switch—improves the native composition of grasslands. We review literature that reports instances where there has been a change in disturbance type to examine how grasslands respond to disturbance switching. We found mostly no change in native and exotic species richness when management changed from stock grazing to fire (at least in the short term, ≤10 years). Positive outcomes for other disturbance shifts (grazing → mowing, or cultivation → grazing) occurred when the disturbance type was accompanied by seed addition, or in landscapes where dispersal from nearby remnant sites was possible. This suggests that seed‐ and/or dispersal‐limitation may limit passive restoration outcomes in fragmented landscapes. It is necessary to determine the longer‐term impacts of switches in disturbance regimes, and whether recovery thresholds have already been crossed.